Chlamydia Trachomatis Infection: Their potential implication in the Etiology of Cervical Cancer - Yang, Xingju (J Cancer, 2021)
Pathogenic bacterial strains can alter the normal function of cells and induce different levels of inflammatory responses that are connected to the development of different diseases, such as tuberculosis, diarrhea, cancer etc. Chlamydia trachomatis (C. trachomatis) is an intracellular obligate gram-negative bacterium which has been connected with the cervical cancer etiology. Nevertheless, establishment of causality and the underlying mechanisms of carcinogenesis of cervical cancer associated with C. trachomatis remain unclear. Studies reveal the existence of C. trachomatis in cervical cancer patients. The DNA repair pathways including mismatch repair, nucleotide excision, and base excision are vital in the abatement of accumulated mutations that can direct to the process of carcinogenesis. C. trachomatis recruits DDR proteins away from sites of DNA damage and, in this way, impedes the DDR. Therefore, by disturbing host cell-cycle control, chromatin and DDR repair, C. trachomatis makes a situation favorable for malignant transformation. Inflammation originated due to infection directs over production of reactive oxygen species (ROS) and consequent oxidative DNA damage. This review may aid our current understanding of the etiology of cervical cancer in C. trachomatis-infected patients.